2005
DOI: 10.1039/b501105a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and speciation studies of heterobimetallic pyridinehydroxamate-bridged Pt(ii)/M(ii) complexes (M = Cu, Ni, Zn). Crystal structure of a novel heterobimetallic 3-pyridinehydroxamate-bridged Pt(ii)/Cu(ii) wave-like coordination polymer

Abstract: The reaction of cis-[Pt(NH3)2(3-pyhaH)2]2+ (3-pyhaH = 3-pyridinehydroxamic acid) and cis-[Pt(NH3)2(4-pyhaH)2]2+ (4-pyhaH = 4-pyridinehydroxamic acid) with Cu(II), Ni(II) or Zn(II) in aqueous solution affords novel heterobimetallic pyridinehydroxamate-bridged complexes, {cis-[Pt(NH3)2(mu-3-pyha)M(mu-3-pyha)].SO4.xH2O}n and {cis-[Pt(NH3)2(mu-4-pyha)M(mu-4-pyha)].SO4.xH2O}n respectively. The crystal and molecular structure of one of these, {cis-[Pt(NH3)2(mu-3-pyha)Cu(mu-3-pyha)]SO4.8H2O}n 3a, has been determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…[4] We also recently utilised 3-and 4-pyridinehydroxamic acids 3-and 4-pyhaH as bridging scaffolds in the design of Pt II /M II coordination polymers (M = Cu, Ni or Zn) because they can coordinate Pt II in a monodentate fashion through the pyridine nitrogen atom only, thus leaving the hydroxamic acid moiety free to coordinate to a separate metal ion (Figure 2). [6] …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[4] We also recently utilised 3-and 4-pyridinehydroxamic acids 3-and 4-pyhaH as bridging scaffolds in the design of Pt II /M II coordination polymers (M = Cu, Ni or Zn) because they can coordinate Pt II in a monodentate fashion through the pyridine nitrogen atom only, thus leaving the hydroxamic acid moiety free to coordinate to a separate metal ion (Figure 2). [6] …”
Section: Introductionmentioning
confidence: 97%
“…[3] The powerful metal-chelating ability of hydroxamic acids has been utilised to spectacular effect in the construction of a diverse host of fascinating metal complexes. These include hydroxamates, [4] hydroximates [4] and examples in supramolecular chemistry such as metallacrowns, [5] coordination polymers [6] and tetrahedral cluster complexes. [7] [a] Centre As ligands, hydroxamic acids typically coordinate in an O,OЈ-bidentate chelating fashion, coordinating through the carbonyl oxygen atom and the deprotonated hydroxy group to form very stable five-membered chelates.…”
Section: Introductionmentioning
confidence: 99%
“…Although hydroxamic acids are known to be strong metal ion chelators, 16,17 we previously reported that they have a low affinity for Pt. [18][19][20] We were therefore confident that the Pt would bind selectively to the malonato substituent. We also believed it important that the two functional entities of the Pt-HDACi conjugate, upon reaching the nucleus, would separate to allow each to work independently of the other.…”
mentioning
confidence: 97%
“…Besides that, frequent solvent-induced polymorphism of Pt(II) complexes with bipyridine [10], polypyridine [11] or diimine ligands [12] that have extended p systems has been shown p-stacking and direct Pt-Pt interactions result in the formation of excimers with the characteristic luminescence shifted to lower energies with respect to the luminescence from monomers. Nevertheless, research of the role of weak coordination interactions between the well-defined monomers which modulates the luminescence properties of the chromophores is relatively limited [13].…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, frequent solvent-induced polymorphism of Pt(II) complexes with bipyridine [10], polypyridine [11] or diimine ligands [12] that have extended p systems has been shown p-stacking and direct Pt-Pt interactions result in the formation of excimers with the characteristic luminescence shifted to lower energies with respect to the luminescence from monomers. Nevertheless, research of the role of weak coordination interactions between the well-defined monomers which modulates the luminescence properties of the chromophores is relatively limited [13].Based on the supramolecular photochemistry of the reported Pt-salen Schiff base systems [9], complexes of platinum(II) and MeO-substituted salen-type Schiff-base could be chosen to develop new systems, in which the outer MeO donors of MeO-salen ligand endows further coordination, definitely directing the stacking of monomers (Pt-MeO-salen) to form structurally diverse and potentially important excimers in their photochemistry applications. Herein, the self-assembly of the Pt-MeO-salen (MeO-salen = N,N 0 -bis(3-methoxy-salicylidene)-ethylene-1,2-diamine) precursor with K 2 Ni(CN) 4 leads to a polymeric complex [K 2 -(Pt-MeO-salen) 2 Ni(CN) 4 ] n Á 0.5nEt 2 O (1), and its improved photoluminescence has been examined.…”
mentioning
confidence: 99%